Technology and innovation in the Covid-19 pandemic: a bibliometric analysis (Research, Society and Development, 2022)
This article aims to analyze the Brazilian scientific production regarding technology and innovation applied to health in the COVID-19 pandemic. Bibliometric study that analyzed national publications, with emphasis on authors, institutions, journals, area of ​​knowledge, year of publication, and mapping of the co-occurrence of keywords, recorded in the Web of Science (WoS) database. The keywords were used: "Technology", "Innovation", "Health" (in Portuguese and English), "COVID-19", "Coronavirus", and "SARS-CoV-2". Descriptive statistical analysis comprised the period from 2019 to 2022, and was supported by Excel and VOSviewer software. The results of this research show that the publications were concentrated in the year 2021 (60.0%), in the Public Environmental Occupational Health category of WoS (22.2 %), in universities in Southeast Brazil, with emphasis on the University of São Paulo (22.5%), in the journal Revista da Sociedade Brasileira de Medicina Tropical (2.4%) and in the authors Giovanetti, M., Ciccozzi, M. & Durigon, E. L., and these authors together produced another 50 published articles. In the co-occurrence map, it was possible to identify the set of keywords that characterize the development of technology and innovation in health during the COVID-19 pandemic, with emphasis on the development of vaccines, therapies and diagnostic tests to face nt of the pandemic. In this way, it is concluded that the Brazilian scientific production on technology and innovation during the COVID-19 pandemic was produced in multidisciplinary articles and was mainly focused on the area of ​​diagnosis, treatment, and vaccine. However, it reinforces the need to advance these studies with different methods in the context discussed.